The differential expression profiles of miRNA in serum-derived exosomes and its potential role in age-related hearing loss - Zhang, Juhong; Ma, Haizhu; Ke, Jing; Tang, Ziyi; Chen, Zhiji; Yang, Guijun; Yang, Li; Guo, Jialin; Yan, Xiaoqi; Peng, Changxiu; Wang, Kaiye; Chen, Xiyao; et al. (Frontiers in Aging Neuroscience, 2026)
ObjectivesThis study aimed to characterize serum exosomal miRNA profiles from patients with age-related hearing loss (ARHL) to identify key pathogenesis-related miRNAs for ARHL.MethodsPeripheral venous blood samples were collected from patients with ARHL and elderly controls, and exosomes were isolated from serum of each subject. Then, the isolated exosomes were systematically identified by nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM) and western blot. Subsequently, the isolated exosomes were submitted for miRNA sequencing and a series of bioinformatics analysis. Ultimately, four key DE-miRNAs, namely hsa-miR-100-5p, hsa-miR-23b-3p, hsa-miR-373-3p, and hsa-miR-27b-3p, were verified using quantitative real-time polymerase chain reaction (RT-qPCR).ResultsNTA, TEM and western blot confirmed exosomes were successfully isolated. After sequencing, 22 differential expressed miRNAs (6 up-regulation and 16 down-regulation) were identified between the exosomes from ARHL and controls, and then collectively identified 17,451 predicted target genes and 15,863 experimentally validated target genes. Gene Ontology enrichment analysis revealed that the target genes were significantly associated with “regulation of neuron projection development,” “sensory system development,” “proteasome-mediated ubiquitin-dependent protein catabolism,” and “ubiquitin-like protein ligase binding.” Kyoto Encyclopedia of Genes and Genomes (KEGG) showed the target genes were significantly enriched in “PI3K-Akt signaling pathway,” “MAPK signaling pathway,” “cellular senescence,” “autophagy,” “mTOR signaling pathway,” “ubiquitin-mediated proteolysis,” and “signaling pathways regulating stem cell pluripotency.” Additionally, the Reactome analysis highlighted the involvement of “MAPK family signaling cascades,” “negative regulation of the PI3K/AKT network,” and “antigen processing: ubiquitination and proteasome degradation.” Disease Ontology further demonstrated significant enrichment of target genes in neurological disorders. RT-qPCR showed hsa-miR-100-5p and hsa-miR-23b-3p exhibited markedly decreased levels, while hsa-miR-373-3p and hsa-miR-27b-3p were significantly up-regulated in ARHL, which were consistent with sequencing results, confirming a high relatively reliability of the sequencing results.ConclusionUbiquitination modification, autophagy process, cellular senescence and nervous system regulation may jointly contribute to the core molecular mechanism of ARHL. The hsa-miR-100-5p, hsa-miR-23b-3p, hsa-miR-373-3p, and hsa-miR-27b-3p may preliminarily act as key regulatory factors to participate in the pathophysiological process of ARHL, providing exploratory evidence for their potential application value as molecular markers.